2016
DOI: 10.1016/j.rbr.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome metabólica em pacientes com diagnóstico de artrite reumatoide acompanhados em um Hospital Universitário do Nordeste brasileiro

Abstract: RA patients in a tertiary center in Northeastern Brazil showed high prevalence of MS. It is worth noting that almost all patients had MS and abdominal obesity, which has important practical implications. In addition to the components of MS, age and smoking were associated with this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
5
0
3
Order By: Relevance
“…In Europe the prevalence rates reported, according to criteria used were: AHA (27.4%), IDF (35.2%), IDF-AHA (37.2%) and NCEP-ATP III (23.0%)[23]. Furthermore, based on the NCE-P-ATP III criteria, Oliveira et al found that the prevalence of MetS among RA patients in South American was 51.4%, but using the IDF criteria this proportion was 53.4% [24]. Much larger differences have been reported in research from the UK, with MetS prevalence ranging from 8.2% to 42.6% [25], depending upon the definition used.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe the prevalence rates reported, according to criteria used were: AHA (27.4%), IDF (35.2%), IDF-AHA (37.2%) and NCEP-ATP III (23.0%)[23]. Furthermore, based on the NCE-P-ATP III criteria, Oliveira et al found that the prevalence of MetS among RA patients in South American was 51.4%, but using the IDF criteria this proportion was 53.4% [24]. Much larger differences have been reported in research from the UK, with MetS prevalence ranging from 8.2% to 42.6% [25], depending upon the definition used.…”
Section: Discussionmentioning
confidence: 99%
“…The findings demonstrate the difficulty in having a diagnostic criterion that is accurate, sensitive, and specific and that can be useful for assessing the general population, overcoming the limitations of regional specificities. Oliveira et al 28 showed the prevalence of MetS in the population with rheumatoid arthritis treated at the Rheumatology Outpatient Clinic of Hospital Universitário Walter Cantídio of Universidade Federal do Ceará, Ceará, Brazil, to be 53.4% by the IDF criteria and 50% by the NCEP-ATPIII criteria. Xi et al 29 used data from the China Health and Nutrition Surveys in 2009 to describe the prevalence of MetS in China and showed that the prevalence in men according to revised NCEP-ATPIII criteria for Asians was 20.9%, according to IDF criteria was 16.2%, and according to the Chinese Diabetes Society criteria was 12.2%.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, studies estimating the prevalence of MetS for urban regions in the southeast reported 29.8% in 2007 30 and 25.4% in 2008 31 by the NCEP-ATPIII criteria, 35.5 and 46.0% in 2007 21 by the NCEP-ATPIII and IDF criteria respectively, 34.0% in 2011 32 by IDF criteria, 35.9 and 43.2% in 2011 33 by the NCEP-ATPIII and IDF criteria, respectively, and 45.2, 64.1, 69.1, and 51.9% in 2014 19 by the NCEP-ATPIII, IDF, Joint Interim Statement (JIS), and WHO criteria, respectively. According to the Brazilian region, the prevalences have been estimated as follows: in the Northeast, 50% by the NCEP-ATPIII criteria and 53.4% by the IDF criteria in 2016; 28 in the South, 50.3% by the ATPIII criteria, 53.4% by ATPIII reviewed by the AHA/NHLBI criteria, and 56.9% by the IDF criteria in 2009; 22 and in the Midwest region, 32.0% by the harmonized MetS criteria 3 in 2012. 34 In a rural population of southeastern Brazil, the MetS was found in 21.6% in 2007 35 and 14.9% in 2011 36 by the NCEP-ATPIII criteria, and in the northeastern region, the MetS was found in 24.8% by the NCEP-ATPIII criteria in 2006.…”
Section: Discussionmentioning
confidence: 99%
“…[ 70 ] In another study in Brazil on RA patients, 110 patients with RA were evaluated and they showed a very high prevalence of MeTS markers such as abdominal obesity (98.1%), HTN (80%), and low HDL (72.2%). [ 71 ]…”
Section: Dermatologic Drug Therapy and Metabolic Syndromementioning
confidence: 99%